Analisis Proses Pembelajaran Dalam Jaringan (Daring) Di Masa Pandemi Covid-19 Pada Mahasiswa - Alfania Salsabilla; Cloudia Yolanda; Destrya Darma Putri; Heriyanto Heriyanto; Tasya Adinda Putri; Jeni Wardi (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2021)
This research intends to gather objective data on online learning activities for students at Lancang Kuning University's Faculty of Economics, based on the policy of studying at home during the COVID-19 emergency response period. The descriptive research method was applied in the form of survey research. The data was collected via indirect communication tactics and data gathering platforms, such as the distribution of surveys using Google Forms. The participants in this study were 100 students from two majors at Lancang Kuning University's Faculty of Economics. Students' online learning activities during the COVID-19 emergency reaction period on the policy of studying at home are "good enough," according to the findings of this study. With the force majeure situation and all of the challenges and hurdles that exist, it is anticipated that it may be used as an evaluation and experience in online learning for both students and lecturers in the future. Abstrak Penelitian ini bertujuan untuk mengumpulkan data objektif kegiatan belajar online bagi mahasiswa Fakultas Ekonomi Universitas Lancang Kuning, berdasarkan kebijakan belajar di rumah selama masa tanggap darurat COVID-19. Metode penelitian deskriptif diterapkan dalam bentuk penelitian survei. Data dikumpulkan melalui taktik komunikasi tidak langsung dan platform pengumpulan data, seperti distribusi survei menggunakan Google Formulir. Partisipan dalam penelitian ini adalah 100 mahasiswa dari dua jurusan di Fakultas Ekonomi Universitas Lancang Kuning. Aktivitas belajar online siswa pada masa tanggap darurat COVID-19 terhadap kebijakan belajar di rumah “cukup baik”, demikian hasil temuan penelitian ini. Dengan situasi force majeure serta segala tantangan dan rintangan yang ada, diharapkan dapat dijadikan sebagai bahan evaluasi dan pengalaman dalam pembelajaran online baik bagi mahasiswa maupun dosen kedepannya